Assessment of Psychopathic Traits: A Case Study - Muttahid Shah, Sadaf Tabassum, Sana Nouman, Rabbia Ashraf, (Pakistan Journal of Medical & Health Sciences, 2024)
Purpose: Present study aim to psychologically accessed a case study of a suspected psychopathic individual Method: Single n subject design was used to investigate a 24 years old male from Peshawar. his case was assessed based on his background history using several assessment measures including the Psychopathic Checklist, House Tree Person (HTP) and GAVEL assessment. Findings: Results confirmed subject ABC's psychopathic characteristics, such as a lack of empathy, remorse, and moral integrity. Conclusion: Subject's evaluation shows a troubling picture with a clear hostile and aggressive personality. Person had lack of remorse and empathy and was much interested in violence, stealing and hurting people. Moreover, materialistic and manipulative characteristic were prominent in him and he often put on a socially acceptable act in front of other while hiding his dark urges. Keywords: drug addiction, psychopath personality trait, GAVEL assessment, HTP